The games of imitation: AI and a philosophy towards future equilibrium - Todd J. Barry (Faculty of Economics and Business, University of Muhammadiyah Malang, 2020)
This brief conceptual article starts with an argument for Artificial Intelligence (AI)’s ability to “think.” This outgrowth relates to human’s and AI’s power over nature, and to AI’s increasing power in its humanness, measured by the results of competing with humans and other AI machines in the Turing Test, and economic “game theory.” Both, and especially the latter challenge, can be quintessentially human by measuring how one values the self as opposed to society, under varying conditions. Given AI’s advancements enabling it to presumably “win” in the most humanness of games, beyond even reaching a universally beneficial “social optimal” outcome, and thus possibly even having more power than humankind, the article argues for an equilibrium of balanced powers in innovation between AI and humans. Therefore, managers, broadly construed, can function as key brokers between government policy makers and innovators as AI and humans continue to develop further into the future.